1995
DOI: 10.1172/jci117807
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic predictors of obesity. Contribution of resting energy expenditure, thermic effect of food, and fuel utilization to four-year weight gain of post-obese and never-obese women.

Abstract: This prospective study was designed to identify abnormalities of energy expenditure and fuel utilization which distinguish post-obese women from never-obese controls. 24 moderately obese, postmenopausal, nondiabetic women with a familial predisposition to obesity underwent assessments of body composition, fasting and postprandial energy expenditure, and fuel utilization in the obese state and after weight loss (mean 12.9 kg) to a post-obese, normal-weight state. The post-obese women were compared with 24 never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
90
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(99 citation statements)
references
References 21 publications
8
90
1
Order By: Relevance
“…31,32 Here, we confirm our previous finding that RMR and long-term body weight changes are negatively related.…”
Section: Discussionsupporting
confidence: 91%
“…31,32 Here, we confirm our previous finding that RMR and long-term body weight changes are negatively related.…”
Section: Discussionsupporting
confidence: 91%
“…The authors suggested that there may be a differential regulation of body-weight gain between lean and overweight populations (8). The previous studies that showed no relation between the REE and weight change included relatively small numbers of subjects (11) or used skinfold thicknesses to measure body composition (which is a suboptimal body-composition approach to adjusting BMR) in men only (7). For these reasons, neither study definitively addressed the question of BMR and weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported both metabolic adaptation to weight loss [14][15][16][17] and no metabolic adaptation [19][20][21][22][23], and factors such as ongoing weight loss and lack of accounting for body fat change as well as FFM change may help explain the variability in results [26]. However, in our study, TEE was lower than expected based on the changes in fat and FFM (at 12 months of CR by approximately 0.76 MJ/d (180 kcals/d), equivalent to 6.6% of baseline TEE) suggesting an adaptive response to the long-term CR that may contribute to the recognized risk of weight regain following weight loss in mildly overweight individuals such as those studied here [58].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic adaptation can be defined as a change in energy expenditure with weight gain or loss over and above that accounted for by the change in body fat free mass (FFM) and fat mass, and may potentially impact long-term weight loss success. Some studies have reported that metabolic adaptation occurs during weight loss and/or subsequently [11][12][13][14][15][16][17][18] while others have found no evidence for this phenomenon [19][20][21][22][23][24][25]. In part, the different results obtained may be due to different mathematical approaches to calculating metabolic adaptation, as well as the duration and severity of caloric restriction (CR) [26].…”
Section: Introductionmentioning
confidence: 99%